Kajian Kliniko-patologik dan Antimikroba Ekstrak Biji Alpukat (Persea Americana Mill) - Christin Marganingsih Santosa; Imron Rosyadi; Dinar Arifianto; Salasia Isrina Oktavia Siti (Jurnal Sain Veteriner, 2019)
The phytochemical components of avocado seeds (Persea americana Mill) consist of alkaloids, flavonoids, tannins and saponins, so that they have the potential as antibacterials. The aim of this study was to determine the ability of Persea americana Mill extract to inhibit the growth of Staphylococcus aureus through inhibition zone observation and the ability to accelerate wound healing infected by S. aureus through observation of wound closure and cytopathology.  Persea americana Mill were extracted using maceration method with 70% ethanol. The activities of this extract were tested by diffusion disc agar method. Biomedical tests were carried out on anaestetic Wistar rats whose were S. aureus infected wounds  and treated with Persea Americana Mill extract. Based on the results of the antimicrobial test, avocado seed extract has a inhibitory effect on the growth of S. aureus at a concentration of 6.25% and best at a concentration of 100% compared to the control. Tests in experimental rats showed the effect of wound healing on the 2rd day after giving the extract Persea americana Mill ointment, faster than the control, which was need 4 days of wound closure. Cytopathology results showed that leukocyte activity was more prominent in rats treated with avocado seed extract compared to control rats. Avocado seeds as byproducts have the potential to be new herbal medicines that can be used as antimicrobials of S. aureus which have been confirmed to be resistant to various antibiotics.